ANALISIS PREFIKS PENANDA NEGASI MU- (無-), FU- (不-), HI- (非-), MI- (未-), HAN- (反-) DALAM BAHASA JEPANG - Widyawati, Intan; rosliana, lina; Trahutami, Sriwahyu (Japanese Literature, 2016)
The purpose of this research is to identify the sructures and meanings of prefixmu-, fu-, hi-, mi-, and han- as negation sign. The author chose this title due thelack of explanation and words examples about the using of those prefix asnegation sign in Japanese textbooks, beside that there were still many mistakes inusing prefix mu-, fu-, hi-, mi-, and han-.The method that been used in this research is a descriptive method. To write thisthesis, firstly, the author collected the data, analyzed the data and then presentedthe result. Prefix mu-, fu-, hi-, mi-, and han- can be attached with noun andadjective in kango, wago, gairaigo, and konshugo. Prefix mu-,fu-, and hi- havethe same meaning as ”not” and “without” in Indonesian language, but actuallythey have the other meanings that can differentiate each other.